Tiga Aspek Penting dalam Kesehatan - Riny Natalina; Happy Marthalena Simanungkalit; Titik Istiningsih; Aisyah Nurjanah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Abstract – Humans place a high value on their health. Health is influenced by a variety of factors, including diet, exercise, stress levels, personality, and behavior. A decent quality of life is influenced by excellent health. The three key facets of health—physical, mental, and social—are the focus of this study. The findings of the study indicate that wellbeing includes not only physical but also mental and social wellbeing. These are three crucial and connected facets of health. Our health can be impacted by a healthy diet, enough sleep, exercise, stress reduction, and social connection. The purpose of this study is to enlighten readers on the significance of considering one's physical, mental, and social health because it influences one's quality of life.